IT Computer Training Programming with PHPRad for Students of Politeknik STIBISNIS Tegal - Budiraharjo, Eko; Firmansyah, Hasbi; Sofyan, Ali; Sari, Nadya Permata (Universitas Pancasakti Tegal, 2024)
The implementation of community service activities in the form of